Urinary Hepcidin-25 Is Elevated in Patients That Avoid Acute Kidney Injury Following Cardiac Surgery. Issue 1 (23rd January 2018) - Choi, Nora; Rigatto, Claudio; Zappitelli, Michael; Gao, Ang; Christie, Simon; Hiebert, Brett; Arora, Rakesh C.; Ho, Julie
Background: Acute kidney injury (AKI) following cardiac surgery leads to increased morbidity and mortality. Characterization and validation of early biomarkers of AKI may ultimately facilitate early therapeutic intervention. We have previously identified that elevated urinary hepcidin-25 is inversely and independently associated with the development of AKI in adult cardiac surgery patients. Hepcidin-25 is an antimicrobial peptide that sequesters iron intracellularly, and its elevation following human ischemia reperfusion injury may represent a renoprotective response to minimize renal injury. Objective: Our goal was to validate urinary hepcidin-25 as a non-invasive biomarker in an independent cardiac surgery cohort, within the context of clinical AKI predictors. Design: Prospective observational cohort study. Setting: Adult cardiac surgery program at St. Boniface Hospital, Winnipeg, Manitoba, Canada. Patients: Adult cardiac surgery patients undergoing cardiopulmonary bypass (CPB), n = 306. Measurements: Urine hepcidin-25, measured on post-operative day (POD) 1. Methods: A prospective, observational cohort of adult CPB patients (n = 306) was collected with serial perioperative urine samples. Urine hepcidin-25 at POD 1 was measured by competitive ELISA. Its diagnostic performance was evaluated in conjunction with clinical parameters and the Thakar clinical prediction score, using multivariate logistic regression. Results: Urinary hepcidin-25 is elevated following cardiac surgery in AKI and non-AKI patients. Elevated urinary hepcidin-25 concentration was inversely associated with AKI on both univariate (odds ratio [OR]: 0.61, 95% confidence interval [CI]: 0.45-0.83, P = .002) and multivariate analysis (OR: 0.67, 95% CI: 0.50-0.95, P = .02). A combined model with clinical risk factors demonstrated that baseline estimated glomerular filtration rate (eGFR), diabetes mellitus, and urinary hepcidin-25 concentration had an overall area under the curve (AUC) of 0.82 (0.75-0.88) for predicting subsequent AKI development, which was superior to clinical prediction alone as determined by the Thakar score. Limitations: (1) A single-center observational study. (2) Polyclonal antibody–based competitive ELISA. Conclusion: Hepcidin-25 is inversely associated with AKI in a multivariate model when combined with eGFR and diabetes mellitus, with an overall AUC of 0.82. Notably, urinary hepcidin-25 improves on clinical AKI prediction compared to the Thakar score alone.